Shaking the Invisible Hand Complexity, Endogenous Money and Exogenous Interest Rates - Moore, B. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
This book makes the case that economies are complex systems and in response to this, develops a unique dynamic nonequilibrium process analysis of macroeconomics. It provides a brief introduction to complex systems, chaos theory and unit roots. The importance and implications of contingency for economic behaviour are developed.